Pengaruh Kode Etik Profesi Akuntan Publik terhadap Kualitas Audit Auditor Independen di Surabaya - Primaraharjo, Bhinga; Handoko, Jessica (Widya Mandala Surabaya Catholic University, 2011)
The study was designed to analyze the effect of the principles of integrity, objectivity, competence, and professionalism of the independent auditor on audit quality. The object of this research is independent auditors in Surabaya. The research data obtained from questionnaire data which the amount of data are 35 respondents. The data analysis technique used is by using test validity, reliability, and linear regression with the help of SPSS for windows. The results showed that the principles of integrity, objectivity, and professionalism have no significant effect on audit quality, while the principle of competence have a significant effect in audit quality. From these results, independent auditors should be concern in competence to create a good audit quality.